2000
DOI: 10.1111/1468-5957.00337
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Implied Volatility: A Test Using LIFFE Option Prices

Abstract: This paper presents and tests a model of the volatility of individual companies' stocks, using implied volatilities derived from option prices. The data comes from traded options quoted on the London International Financial Futures Exchange. The model relates equity volatilities to corporate earnings announcements, interest-rate volatility and to four determining variables representing leverage, the degree of fixed-rate debt, asset duration and cash flow inflation indexation. The model predicts that equity vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…First, unconditional on earnings news, we find a general increase in implied volatility in the 10 days leading up to an earnings announcement, followed by a significant decline in implied volatility immediately subsequent to the earnings announcement. This confirms findings in prior studies, which generally found a build-up in uncertainty in the immediate pre-announcement period manifested by rising implied volatility, then a resolution of the uncertainty accompanying the release of earnings news manifested by a decline in implied volatility Wolfson, 1979, 1981;Donders and Vorst, 1996;Copeland et al, 2000;Donders et al, 2000;Isakov and Perignon, 2001;Acker, 2002). 4 Both the run-up of implied volatility in the pre-announcement period and the decline of implied volatility in the post-announcement period are most pronounced for options with shorter maturities and less so for options with longer maturities, which suggests that the impact of earnings announcements on expected future volatility is transitory.…”
Section: Introductionsupporting
confidence: 87%
“…First, unconditional on earnings news, we find a general increase in implied volatility in the 10 days leading up to an earnings announcement, followed by a significant decline in implied volatility immediately subsequent to the earnings announcement. This confirms findings in prior studies, which generally found a build-up in uncertainty in the immediate pre-announcement period manifested by rising implied volatility, then a resolution of the uncertainty accompanying the release of earnings news manifested by a decline in implied volatility Wolfson, 1979, 1981;Donders and Vorst, 1996;Copeland et al, 2000;Donders et al, 2000;Isakov and Perignon, 2001;Acker, 2002). 4 Both the run-up of implied volatility in the pre-announcement period and the decline of implied volatility in the post-announcement period are most pronounced for options with shorter maturities and less so for options with longer maturities, which suggests that the impact of earnings announcements on expected future volatility is transitory.…”
Section: Introductionsupporting
confidence: 87%
“…Such changes may arise as a response to changes in macroeconomic or microeconomic conditions (see, for example, Copeland et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have analysed various scheduled announcements: twelve macroeconomic announcements (Ederington and Lee, 1996), three macroeconomic announcements (Li & Engle, 1998), company earnings (Patell & Wolfson, 1979, 1981, Donders & Vorst, 1996, Copeland, Poon & Stapleton, 2000, the balance of trade (Madura & Tucker, 1992), the money supply (Bailey, 1988), a general election (Gemmill, 1992) and interest rate changes (Bomfim & Reinhart, 2000). Other studies have looked at the effects of unscheduled announcements on implied volatility: ten major news announcements (Cornell, 1978), takeovers (Barone-Adesi, Brown & Harlow, 1994), mergers (Jayaraman et al, 1991, Levy & Yoder, 1993, interest rate changes (French & Fraser, 1986), the effect of the Louvre Accord on volatility in currency markets (Tucker & Madura, 1991), central bank intervention in the foreign exchange market (Bonser-Neal, 1996, Bonser-Neal & Tanner, 1996 and dividend increases (Jayaraman & Shastri, 1993).…”
Section: The Effects Of Scheduled Announcements On Short Sterling Optmentioning
confidence: 99%